Cepharanthine Inhibits Fusarium solani via Oxidative Stress and CFEM Domain-Containing Protein Targeting - Yuqing Wang; Zenghui Yang; Jingwen Xue; Yitong Wang; Haibo Li; Zhihong Wu; Yizhou Gao (Microorganisms)
Cepharanthine (CEP) is a natural bisbenzylisoquinoline alkaloid known for its antibacterial, antiviral, and anti-inflammatory activities. Its antifungal effect, however, has not been well studied. In this work, we used machine learning-based virtual screening with Random Forest, Neural Network, and Support Vector Machine models to identify potential inhibitors of Fusarium solani. CEP was selected as a candidate and tested experimentally. The results showed that it inhibited the growth of Fusarium solani, Fusarium proliferatum, Fusarium oxysporum, Alternaria alternata, and Botrytis cinerea. It also reduced the sporulation and spore germination of Fusarium solani and disrupted its redox balance. Transcriptome analysis showed changes in gene expression related to basic metabolic pathways. Molecular docking suggested that CEP binds to the FsCFEM1 protein, and molecular dynamics simulations confirmed stable binding, with key roles for residues THR748 and LEU950. These results suggest that CEP is a potential bio-based antifungal agent and provide novel insights into its mechanism against Fusarium solani.